Penerapan Metode Forward Chaining Untuk Sistem Pakar Diagnosis Penyakit Tanaman Mentimun Berbasis Web - Baswardono, Wiyoga; Nurfadillah , Rifa Sri (Institut Teknologi Garut, 2025)
Cucumber is a horticultural crop that plays an important role in Indonesia but often suffers from diseases that hinder harvest yields. There is a lack of information regarding cucumber diseases, their symptoms, care methods, and appropriate actions for treatment. This study aims to develop a web-based expert system for diagnosing cucumber diseases using the Forward Chaining method. The system is designed using the Rational Unified Process (RUP) methodology, which includes four phases: Inception, Elaboration, Construction, and Transition. Application testing was conducted using Blackbox Testing across seven test stages, all of which yielded results as expected. Meanwhile, Beta Testing with User Acceptance Testing (UAT) involving 30 users resulted in a satisfaction rate of 83.8%, and testing by 2 administrators produced a score of 90.00%. Based on the Likert scale assessment, these results fall into the